A production-repair inventory model with time-varying demand and multiple setups - Omar, M.; Yeo, I. (2014)
demand for a finished product over a known and finite planning horizon by supplying both new and repaired items. New items are fabricated from a single type of raw material procured from external suppliers. while used items are collected from the customers and then repaired to a condition that is as good- as-new. During each time interval. new items and used items are produced from multiple production and repair runs. The problem is to determine a joint policy for raw materials procurement. new items fabrication, and used items repair such that the total relevant cost of the model is minimized. We also proposed a numerical solution procedure and we tested the model with some numerical examples and a simple sensitivity analysis.